2013
DOI: 10.1007/s10551-013-1928-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Social Responsibility on Organizational Commitment: Exploring Multiple Mediation Mechanisms

Abstract: 18 pagesInternational audienceUnlike previous studies that examine the direct effect of employees' perceived corporate social responsibility (CSR) on affective organizational commitment (AOC), this article examines a mediated link through organizational trust and organizational identification. Social exchange and social identity theory provide the foundation for predictions that the primary outcomes of CSR initiatives are organizational trust and organizational identification, which in turn affect AOC. The tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
446
7
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(522 citation statements)
references
References 90 publications
28
446
7
9
Order By: Relevance
“…Less intention to quit, in turn, helps to stimulate the employees' mind and thoughts to creatively contribute in the organizational activities. In the same vein, previous studies found that CSR activities enhance employees commitment [101][102][103][104].…”
Section: Resultsmentioning
confidence: 76%
“…Less intention to quit, in turn, helps to stimulate the employees' mind and thoughts to creatively contribute in the organizational activities. In the same vein, previous studies found that CSR activities enhance employees commitment [101][102][103][104].…”
Section: Resultsmentioning
confidence: 76%
“…It is basically meaningful that organizations develop and implement socially responsible policies and practices, however, it might be more significant to inform organizational members about CSR efforts. It is thus advisable that organizations communicate their CSR activities in order to strengthen employees' attitudes toward their organization and job [24,59,60]. According to the findings of this study, CSR behaviors play a pivotal role in fostering employees' organizational identification and job satisfaction, and consequently job performance.…”
Section: Theoretical Contributions and Managerial Implicationsmentioning
confidence: 80%
“…These expressions of supplementary public responsibility are valued by employees, who in turn contribute positively to the SMEs. In other words, this type of CSR can increase employee morale, wellbeing, organizational 28 commitment and performance (Farooq et al 2014;Vlachos et al, 2013). A Tanzanian SME succinctly captures this phenomenon:…”
mentioning
confidence: 99%